Extreme Rainfall-Runoff Events Modeling by HEC-HMS Model for Koudiet Rosfa Watershed, Algeria - HADDAD, Ali; REMINI, Boualem (GeoScience Engineering, 2021)
Changing of precipitation regime and intensification of extreme storms in semi-arid regions because of climate change requires the use of numerical models to forecast the outlet hydrographs. In this paper, HEC-HMS software was applied using a loss method the curve number CN to estimate the precipitation excess and a parametric unit hydrograph model to compute the transformation of precipitation excess into direct runoff over the watershed. The Muskingum-Cunge routing model was used to simulate the propagation of direct runoff through the main streams of Koudiet Rosfa watershed. The curve number CN and lag time parameters were used to calibrate the model towards several storms. The Nash–Sutcliffe efficiency coefficient (NSE) was adopted to assess the performance of the model to reproduce the observed hydrographs. Volume of the storms, peak discharges, times of peak and times of center of mass between the simulated and observed discharges were used to validate the model. The simulated discharges reproduce the hydrological events. The calibrated model was used to simulate the different hypothetical storms that could occur in the future in order to ensure the safety of Koudiet Rosfa dam towards extreme rainfall-runoff events. Keywords: HEC-HMS model; Hydrologic model; Rainfall-runoff; Semi-arid region.